In vitro and in vivo evaluation of L‐lactide/ε‐caprolactone copolymer scaffold to support myoblast growth and differentiation. (20th December 2012) - Bandyopadhyay, Balaji; Shah, Viru; Soram, Memtombi; Viswanathan, Chandra; Ghosh, Deepa
Abstract: Skeletal muscle regeneration involves the activation of satellite cells to myoblasts, followed by their proliferation and fusion to form multinucleated myotubes and myofibers. The potential of in vitro proliferated myoblasts to treat various diseases and tissue defects can be exploited using tissue‐engineering principles. With an aim to develop a biocompatible and biodegradable scaffold that supports myoblast growth and differentiation, we have developed a porous sponge with 70/30L ‐lactide/ε‐caprolactone copolymer (PLC) using a phase inversion combined with particulate leaching method. Degradation studies indicated that the sponge retained its structural integrity for 5 months in vitro and had undergone complete biodegradation within 9 months in vivo. The sponge supported human myoblasts attachment and its proliferation. Myoblasts seeded on the PLC sponge differentiated and fused in vitro to form myotubes expressing myosin heavy chain. Histological and molecular analyses of the PLC scaffolds seeded with green fluorescent protein‐labeled human myoblasts and implanted ectopically under the skin in SCID mice demonstrated the presence of multinucleated myotubes expressing human muscle‐specific markers. Our results suggest that PLC sponges loaded with myoblasts can be used for skeletal muscle engineering or for inducing muscle repair. © 2012 American Institute of Chemical Engineers Biotechnol. Prog., 2013